Japan’s Reformed Prosecution Review Commission: changes, Challenges, and Lessons - Johnson, David T. (Asian journal of criminology, 2019)
This article evaluates how Japan’s Prosecution Review Commission (PRC) has performed since it was reformed in 2009 to allow panels of 11 citizens to override the non-charge decisions of professional prosecutors. In the first eight cases of “mandatory prosecution” that have occurred since 2009, the conviction rate is 20%—far lower than Japan’s usual conviction rate, which exceeds 99%. In the ninth case of mandatory prosecution, three former executives of the Tokyo Electric Power Company have been subject to mandatory prosecution for “professional negligence resulting in death and injury,” for failing to prevent the nuclear meltdowns at Fukushima that were precipitated by the earthquake and tsunami of March 11, 2011, which killed 18,500 people and caused 200,000 more to flee their homes. As of 2018, the trial of the Tepco executives is still in progress. This evaluation study of prosecutorial reform in one Asian nation suggests that, in principle, prosecutors’ non-charge decisions can be checked and controlled. In practice, however, Japan’s PRC reform has done little to alter the standard operating procedures of professional prosecutors. Further reform of the PRC may be necessary.